Analysis of Nepalese Consumers’ Insurance Purchase Intention: A Structural Equation Model Approach - Adhikari, Prashant; Khadka, Chakra Bahadur (ILAM इलम, 2025)
In recent years, there has been a spike in the insurance industry in Nepal due to the high risk and financial planning awareness. But when correlated with other nations in South Asia, insurance penetration is low in the country. This research was done to realize the factors that are influencing the buying behavior of insurance in the context of Nepalese consumers. The research used a measurement model executed by reflective measurement model to assess the impact of Agent Influence, Corporate Image, Insurance Technology, Perceived Value, and Service Quality on Purchase Intention. Data for the study was collected through a field survey and online survey consisting of 5- point Likert scale questions. The 301 valid responses were analyzed using descriptive statistics and structural equation modeling to show the casual relationship between the variables. The study reports that Agent Influence, Corporate Image, Perceived Value, and Service Quality all have a significant relationship with Purchase Intention. The most significant factor among them is Agent Influence, which was found to influence Purchase Intention directly and positively. Besides, Service Quality has a direct effect on Purchase Intention. The Corporate Image does not have a direct impact on Purchase Intention, but it creates very huge Perceived Value leading to Purchase Intention. More precisely, Perceived Value significantly enhances Purchase Intention by directly contributing to it. This is strengthened by the impacts of both Service Quality and Corporate Image on purchase intention, through Perceived Value. There is no statistically significant influence found in Purchase Intention for Insurance Technology. Pivotal to the increased intention for insurance are the increasing perceived value and improving quality of service. The study concludes that enhancing perceived value and improving service quality is crucial for increasing purchase intentions.